A protocol for flow cytometric determination of expected chromosome number of Brassica juncea L. introgression lines (Journal of Oilseed Brassica, 2026)
Flow cytometry was used to estimate the amount of DNA in nuclei of a set of Brassica juncea introgression lines carrying genomic segments from B. fruticulosa. Solanum lycopersicum L. cv. ‘Stupicke´ with 2C nuclear DNA content of 1.96 pg was used as an internal reference standard. The 2C DNA content of 2.440 pg was worked out for the standard, B. juncea cv. RLC- 1. The 2C DNA content of B. juncea introgression lines ranged between of 2.248 pg (AD4K2-196) and 2.538 (AD3L-526, AD3L-459). Increase in the genome size as compared to the standard B. juncea parent, RLC 1 may indicate the addition of alien chromatin from B. juncea. A reduction in genome size may indicate the chromatin loss. Results indicated a high correlation (0.84) between the relative nuclear DNA content and the expected chromosome number. The studies showed that flow cytometry can be effectively used to gain more insight into the variation and transmission of DNA content within the alien introgressed populations of crop Brassica species.